Methodological proposal for the development of entrepreneurship in the university environment. - Narváez Vásquez, Germán; Zambrano Paladines, Mario; Zambrano Proaño, Paola (Revista Universidad de Guayaquil, 2018)
In today’s global and highly competitive economy, the universities are increasingly assuming a leading role in the economic development of society, have gone from universities focused on academic training to entrepreneurial universities. The problem occurs because there is no uniform process that allows encourage entrepreneurship in the university environment. The methodology of this study is descriptive exploratory type, considering the empirical assumptions of the literature and evidence of historical data, based on observations in the period (20102013) the object of study. Provide, sensitize, Date and Involve, which would foster a culture of entrepreneurship in students: a methodology that consists of four steps is proposed. The results showed that 90% of the ideas were innovative and 100% of the teams developed their business plans.